Age-associated aberrations of the cumulus-oocyte interaction and in the zona pellucida structure reduce fertility in female mice - Yu Ishikawa-Yamauchi; Chihiro Emori; Hideto Mori; Tsutomu Endo; Kiyonori Kobayashi; Yuji Watanabe; Hiroshi Sagara; Takeshi Nagata; Daisuke Motooka; Akinori Ninomiya; Manabu Ozawa; Masahito Ikawa (Communications Biology)
Abstract, One of the major age-related declines in female reproductive function is the reduced quantity and quality of oocytes. Here we demonstrate that structural changes in the zona pellucida (ZP) were associated with decreased fertilization rates from 34- to 38-week-old female mice, equivalent to the mid-reproductive of human females. In middle-aged mouse ovaries, the decline in the number of transzonal projections was accompanied by a decrease in cumulus cell-oocyte interactions, resulting in a deterioration of the oocyte quality. Scanning electron microscopy showed the ZP surface microfilament structure transitioning from rugged to smooth with aging, leading to decreased fertilization rates due to impaired sperm binding to the ZP. Moreover, the fertilization rate of middle-aged mice was restored to a comparable level to that of young mice by destabilizing the ZP in the presence of glutathione. These results suggest that the age-related structural changes in the ZP are key for successful fertilization at reproductive age.